2017
DOI: 10.1021/acs.biomac.7b00553
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer Molecular Weight Can Modulate the Wound Healing Efficacy of Multivalent Sonic Hedgehog–Hyaluronic Acid Conjugates

Abstract: There is a clinical need for new therapeutics to improve healing of chronic impaired wounds. Thus, we investigated how biopolymer conjugation could be used to improve the wound healing performance of a key growth factor for tissue regeneration: Sonic hedgehog (Shh). We generated two multivalent Shh conjugates (mvShh) using hyaluronic acid (HyA) with two different molecular weights (MWs), which exhibited equivalent potency and proteolytic protection in vitro. Using db/db diabetic mice, we showed that mvShh made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Multimodal imaging-guided multistage targeted chemo-photothermal therapy [335] Optimized HA-methotrexate conjugates OA therapy [336] Steroids Steroid grafted on to HA Antioxidant delivery [337] EGF HA-EGF conjugate Chronic wound healing [338] Skin wound healing and regeneration [339] Anti-tumor necrosis factor-α Anti-tumor necrosis factor-α HA conjugate Early healing effects in a rat burn model [340] Epigallocatechin-3-O-Gallate HA-Epigallocatechin-3-O-Gallate conjugates injectable hydrogel Free radical scavenging [341] Sonic hedgehog Sonic hedgehog-HA conjugates Wound healing [342] Multivalent Sonic hedgehog conjugate Diabetic wound healing [343] Catechin Hyaluronic acid-green tea catechin nanogels Targeted intracellular protein delivery [344] Quercetin HA-quercetin conjugated micelles A tumor cell-targeted prodrug [345] Opiods HA-opioid conjugate Controlled delivery treatment for pain alleviation applications [346] Adv. Therap.…”
Section: Methotrexate Coated Magnetic Polydopamine Nanoparticlesmentioning
confidence: 99%
“…Multimodal imaging-guided multistage targeted chemo-photothermal therapy [335] Optimized HA-methotrexate conjugates OA therapy [336] Steroids Steroid grafted on to HA Antioxidant delivery [337] EGF HA-EGF conjugate Chronic wound healing [338] Skin wound healing and regeneration [339] Anti-tumor necrosis factor-α Anti-tumor necrosis factor-α HA conjugate Early healing effects in a rat burn model [340] Epigallocatechin-3-O-Gallate HA-Epigallocatechin-3-O-Gallate conjugates injectable hydrogel Free radical scavenging [341] Sonic hedgehog Sonic hedgehog-HA conjugates Wound healing [342] Multivalent Sonic hedgehog conjugate Diabetic wound healing [343] Catechin Hyaluronic acid-green tea catechin nanogels Targeted intracellular protein delivery [344] Quercetin HA-quercetin conjugated micelles A tumor cell-targeted prodrug [345] Opiods HA-opioid conjugate Controlled delivery treatment for pain alleviation applications [346] Adv. Therap.…”
Section: Methotrexate Coated Magnetic Polydopamine Nanoparticlesmentioning
confidence: 99%
“…Similarly, recent other studies have demonstrated that HA conjugation could increase the activity of proteins. 18,[22][23][24][25][26][27] The cytokine neutralizing HA-antibody conjugates appeared to strengthen the binding affinity for inflammation mediators with the simultaneous activation of CD44/ RHAMM and the suppression of cytokine-signaling networks. 25 The used HA with a MW of 100-300 kDa was also reported to promote wound healing.…”
Section: Effect Of Ha-egf Conjugates On Hacat Cellsmentioning
confidence: 99%
“…The protocol for synthesizing HA-SpyTag is a combination of previous methods. [22][23][24] Every step was performed at 25 °C unless stated. 400 mg of hyaluronic acid (HA) (242 kDa, sodium salt, Lifecore Biomedical LLC) was dissolved in 40 mL ddH2O.…”
Section: Introductionmentioning
confidence: 99%